Bedaquiline Effect on QT Interval of Drugs-Resistant Tuberculosis Patients: Real World Data - I Gusti Agung Ayu Putu Sri Darmayani; Purwantyastuti Ascobat; Instiaty Instiaty; Yani Jane R Sugiri; Neni Sawitri (Interna Publishing, 2022)
Background: Bedaquiline (BDQ) is effective as part of treatment regimen for drug-resistant tuberculosis (DR-TB), but the cardiac safety profile of BDQ is not fully elucidated. This study aimed to analyse the cardiac safety of BDQ by examining its effect on the QT interval of DR-TB patients. Methods: This is a retrospective study cohort conducted in two DR-TB referral hospitals in Indonesia. The QT interval before and after therapy using BDQ was measured manually and corrected using the Fridericia formula (QTcF). The QT interval profile was analysed over time during BDQ treatment. Results: A total of 105 subjects participated in the study. The maximum mean difference (standard deviation) of QTcF after treatment with the baseline (∆QTcF) is 34,06 (52,92) ms after three months of therapy. During BDQ treatment, clinically significant QTcF prolongations was observed in 37.1% subjects with neither arrhythmia nor any other adverse cardiac event occurred. The interval QT prolongation led to BDQ discontinuation in 15.2% subjects temporarily and in 6.7% subjects permanently. There were seven deaths (6.7%) during the treatment. Conclusion: During BDQ treatment, maximum QT prolongation was observed after three months of BDQ therapy. Therefore, more intensive cardiac monitoring is recommended during this period and afterwards.